Legal Foundation for the Establishment of General Procurement Guidelines for Goods and/or Services in Regional Government-Owned Enterprises (BUMD) to Realize Legal Certainty - Anjas Mega Lestari; Budi Santoso; Amelia Sri Kusuma Dewi (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Regional Government-Owned Enterprises (BUMD) are established not only to develop regional economies but are also expected to meet community needs by providing goods or services according to the needs and characteristics of the respective regions while considering the potential of the region itself. To fulfill these objectives, BUMD are managed based on good corporate governance principles, and in running their business and supporting operations, they cannot be separated from activities to procure goods and services. This research is compiled to analyze the legal foundation for establishing general procurement guidelines for goods and/or services in BUMD to realize legal certainty. This research concludes that the regulation of general procurement guidelines for goods/services in BUMD is urgently needed. The need for such regulation is based on philosophical, juridical, sociological, political, ecological, economic, and cultural arguments, so that with the existence of guidelines from the central government, it is expected that the implementation of procurement of goods and services in BUMD can be realized in accordance with the purpose of its establishment and to end regulatory disharmony at the regional level so that legal certainty can be achieved.